Factibilidad para la implementación de una planta procesadora de café tostado y molido tipo artesanal en el cantón Jipijapa - Espinoza Bravo, Joyce Nohely (2021)
The purpose of this study is to determine the feasibility for the implementation of an artisanal roasted and ground coffee processing plant in the Jipijapa canton. The supply and demand of roasted and ground coffee were characterized using a survey of a representative sample of 377 people, based on the universe population of 74.739 inhabitants. A fluctuating price between $3 and $15 per kilogram of roasted and ground coffee was evident; with important marketing channels such as neighborhood stores (70%), general market (20%), supermarkets (5%) and home delivery (5%). Among the main options for the commercialization of the product are AKI, TÍA S.A. and other commercial chains. An analysis of the environmental, technical and infrastructural factors was carried out for the proper georeferencing of the plant in the La América parish, via Jipijapa-Paján, due to the proximity of more than four thousand hectares of coffee distributed in the area. This project estimated an initial investment of $ 91,605, with approximate income of $ 130,069.25 during the first year of management. An NPV of $ 49,378, an IRR of 20% and a breakeven point of $ 102,866.97 was registered. In this way, the financial economic viability for the implementation of the plant was determined. The implementation of the Leopold matrix showed an insignificant incidence of –49 as a consequence of the establishment of the processing plant.